Incentives to invest in abatement technology. A tax versus emissions trading under imperfect competition - Halvor Briseid Storrøsten (Statistics Norway, Research Department, 2010)
In the longer run, effects on R&D and the implementation of advanced abatement technology may be at least as important as short-run cost effectiveness when we evaluate public environmental policy. In this paper, we show that the number of firms that adopt advanced abatement technology could be higher with emissions trading than with a tax if there is imperfect competition in the permits market. Under perfect competition, the number would always be higher with a tax, given that the regulator is myopic. If we allow for environmental policy response, the ranking is still ambiguous under imperfect competition, while the regimes become equal with perfect competition.
Keywords: H23; Q55; Q58; 330; Auctioned permits; Emissions taxes; technology adoption; Cournot competition